Ujrah Sumber Profitabilitas Pada Islamic Microfinance Institutions (BMT) - Eny Lathifah; Ahmad Zuhril Kalam (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2020)
The purpose of this paper is to determine ujrah as a source of profitability in Islamic Microfinance Institutions (BMT Maslahah) in the operationalization of ujrah based contracts. This research method is a qualitative research with a descriptive approach to the case study on BMT Maslahah. The analysis used in this study uses triangulation of data sourced from documentation, observation and interviews directly to respondents in order to get the actual data.The results of this study are ujrah as a source of profitability in Islamic microfinance institutions derived from several aspects of business operations, namely on savings products, financing, services, and sharia investment facilities for members. BMT Maslahah has a superiority with specifications that show a very high profitability value and is permanent, for ordinary savings members can get a bonus balance whose amount is not fixed and if BMT suffers a business loss, members do not need to bear these losses, and for members investing in shares can get a bonus in a large and fixed amount each year and the lack of a contract based on ujrah is in terms of financing and investment stocks, the amount of profit distributed does not follow operating profit.